(3GdJLQHI GdOjebQGWjI hJWhQ fXe GdMce aj GdShOGf (B/ s - (3EHQGgje eMeO GdMGL ehSis; (3KQhJ HOhjs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B:s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 1970)
(3JHOC GdQSGdI HHGH JegjOj Yf JWhQ fXe GdMce efP EYGOI aJM GdShOGf MJi GdGSJbdGd, Ke jCJj GdbSe GdChd Yf eQGMd GdJLQHI GdOjebQGWjI HGdShOGf, Ke GdbSe GdKGfj Yf GdJLQHI GdOjebQGWjI aj Xd OSJhQ SfI (B1956.s
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, (B1970.s
(3HHdjhLQGajG(B: (3UaMGJ (B623-633.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GSJbdGd GdShOGfs; (3GdeLdS GdGSJTGQj dTeGd GdShOGfs; (3GdLeYjI GdJTQjYjI ddShOGfs; (3GdJLQHI GdOjebQGWjI HGdShOGfs; (3fXGe GdMce aj GdShOGf s; (3OSJhQ (B1956 (3aj GdShOGfs; (3eQMdI GdMce GdYScQj aj GdShOGfs; (3KhQI CcJhHQ SfI (B1964s; (3KhQI (B25 (3eGjh SfI (B1969s; (3GdJQcjH GdbHdj hGdWGFaj ddShOGfs; (3GdUQGY GdMRHj aj GdShOGfs; (3eTcdI LfhH GdShOGfs; (3GSJbdGd GdShOGfs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- 1970